A systematic narrative review of extrinsic strategies to improve affective responses to exercise - Leighton Jones; Zachary Zenko (Frontiers Media S.A., 2023)
BackgroundExtrinsic strategies affect the exercise experience but fall outside the frequency, intensity, time, and type (i.e., dose-determining) principles. To our knowledge, no systematic review has focused on extrinsic strategies to influence the affective responses to exercise. The objective was to identify extrinsic strategies that seek to influence affective responses during exercise and other motivationally relevant variables including post-exercise momentary affective valence, remembered and forecasted pleasure, and enjoyment.MethodsFor inclusion, eligible articles reported peer-reviewed original research, used acute bouts of exercise, and used a dimensional approach for measuring affective responses or measured enjoyment post-exercise. Web of Science, PubMed, and PsychINFO databases were last searched on 10th September 2021. Quality assessment was completed following the Effective Public Health Practice Project approach. Results were presented using a narrative synthesis.Results125 studies were included with sample descriptions, study design (extrinsic strategies, mode, type, intensity, and duration), measurement details, and results summarised for each study.Conclusions71% of studies were categorised as Weak according to the quality assessment tool with sampling practices (self-referred participants) and poor reporting of participant withdrawals/drop-outs the predominant reasons for Weak ratings. A wide variety of extrinsic strategies were reported with music, music videos, immersive virtual reality, outdoor exercise, caffeine, high-to-low pattern of exercise intensity, self-selected exercise intensity, and manipulation of self-efficacy offering promise as suitable strategies to positively change how people feel during exercise.Systematic Review Registrationhttps://osf.io/jbh8v/.